CTA442 : Visual culture / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
In this course, students will be able to understand the significance between visual objects and its cultural contexts. This theory-based course focuses on the meaning of imagery which includes fine art, folk art, mass media, design, popular culture, architecture, and other categories of visual phenomena in diverse societies and in everyday life. It is not only a study of images, but a culture’s visual meaning system conveyed in images which involve exploration of the context of the image production and how context alters the meaning.